2021
DOI: 10.3390/ijms22116029
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Monoxide and Nitric Oxide as Examples of the Youngest Class of Transmitters

Abstract: The year 2021 is the 100th anniversary of the confirmation of the neurotransmission phenomenon by Otto Loewi. Over the course of the hundred years, about 100 neurotransmitters belonging to many chemical groups have been discovered. In order to celebrate the 100th anniversary of the confirmation of neurotransmitters, we present an overview of the first two endogenous gaseous transmitters i.e., nitric oxide, and carbon monoxide, which are often termed as gasotransmitters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 152 publications
(214 reference statements)
0
36
0
Order By: Relevance
“…Through excitatory motor neurons, ascending interneurons cause contraction of smooth muscle mediated by acetylcholine, substance P, and neurokinin A. Descending interneurons cause smooth muscle relaxation, activating inhibitory motor neurons to release nitric oxide (NO), vasoactive intestinal peptide (VIP), and pituitary adenylate cyclase-activating peptide (PACAP) [ 17 ]. Longitudinal smooth muscles contract and relax in reverse fashion to circular muscle under the regulation of the same neurotransmitters [ 18 , 19 ].…”
Section: Serotonin In the Gi Tractmentioning
confidence: 99%
See 2 more Smart Citations
“…Through excitatory motor neurons, ascending interneurons cause contraction of smooth muscle mediated by acetylcholine, substance P, and neurokinin A. Descending interneurons cause smooth muscle relaxation, activating inhibitory motor neurons to release nitric oxide (NO), vasoactive intestinal peptide (VIP), and pituitary adenylate cyclase-activating peptide (PACAP) [ 17 ]. Longitudinal smooth muscles contract and relax in reverse fashion to circular muscle under the regulation of the same neurotransmitters [ 18 , 19 ].…”
Section: Serotonin In the Gi Tractmentioning
confidence: 99%
“…Hagbom showed that serotonin is secreted by EC cells in response to rotavirus enterotoxin NSP4, which acts via 5-HT3 receptor and increases bowel motility [ 77 ]. The mechanism of chemotherapy-dependent nausea is via excitation by anticancer drugs (e.g., cisplatin) of EC cells to release serotonin, which activates 5-HT3 receptors and vagal sensory afferent neurons conduct signals to the emetic center in the brain stem [ 17 , 78 ]. In patients treated by cisplatin, higher urinary levels of 5-HIAA confirmed the correlation with the development of emesis.…”
Section: Serotonin In the Gi Tractmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a significant portion of phenotypic changes caused by nitrite are NO-independent, it is widely accepted that NO is the molecule largely underpinning the physiological influences; nitrite impacts the physiology of living organisms in part by serving as a biochemical circulating reservoir for NO [19]. Additionally, NO can be engaged in cellular physiological and pathological processes through a complex cross-talking with two other gasotransmitters, carbon monoxide (CO) and hydrogen sulfide (H 2 S) [23][24][25][26][27]. Meanwhile, nitrite can be converted back to NO through the one-electronoxidation of NO.…”
Section: Introductionmentioning
confidence: 99%
“…However, it was discovered that in mammals H 2 S has physiological relevance and is endogenously generated [ 1 , 2 ]. Currently, H 2 S is considered to be a member of the class of gasotransmitters or, in other words, endogenous gaseous signaling molecules, along with nitric oxide and carbon monoxide [ 3 , 4 , 5 , 6 , 7 ]. Although still debated, cyanide has also recently been proposed to be part of this class [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%